El papel del hierro “libre” y el estrés oxidativo en la etiología del edema de los niños con Kwashiorkor (2005)
ABSTRACT: Kwashiorkor is a serious form of energy-protein malnutrition, different of marasmus in which edema is a major feature. Initial theories explaining this disorder state that low protein intake cause serum albumin deficit, resulting in decreased oncotic pressure, causing water drains into interstitial space. Starting from 1980, several comparative studies had proved that diets of children suffering of either marasmo or Kwashiorkor do not show significant differences in protein content, and a very low protein intake doesn’t result in edematous malnutrition. At the same time researchers found some biochemical alterations in children suffering from kwashiorkor but not in those with marasmus, such as: higher production of oxygen reactivate species, lower antioxidant protection, high ferritine levels, low transferrine levels, and free iron in serum. The above mentioned, allows us to suggest that protein deficiency is not the only decisive factor in the course of severe malnutrition toward kwashiorkor, and that edema could be a consequence for the oxidative damage caused to organic biomolecules by infection and free serum iron.